Multiple genes encode nuclear factor 1-like proteins that bind to the promoter for 3-hydroxy-3-methylglutaryl-coenzyme A reductase. - Gil, G (1988)
DNA-binding proteins of the nuclear factor 1 (NF1) family recognize sequences containing TGG. Two of these proteins, termed reductase promoter factor (RPF) proteins A and B, bind to the promoter for hamster 3-hydroxy-3-methylglutaryl-coenzyme A reductase, a negatively regulated enzyme in cholesterol biosynthesis. In the current study, we determined the sequences of peptides derived from hamster RPF proteins A and B and used this information to isolate a cDNA, designated pNF1/Red1, that encodes RPF protein B. The peptide sequence of RPF protein A, the other reductase-related protein, suggests that it is the hamster equivalent of NF1/L, which was previously cloned from rat liver. We also isolated a hamster cDNA for an additional member of the NF1 family, designated NF1/X. Thus, the hamster genome contains at least three genes for NF1-like proteins. It is likely to contain a fourth gene, corresponding to NF1/CTF, which was previously cloned from the human. The NH2-terminal sequences of all four NF1-like proteins (NF1/Red1, NF1/L, NF1/X, and NF1/CTF), which are virtually identical, contain the DNA-binding domain that recognizes TGG. Functional diversity may arise from differences in the COOH-terminal sequences. We hypothesize that the COOH-terminal domain interacts with adjacent DNA-binding proteins, thereby stabilizing the binding of a particular NF1-like protein to a particular promoter. This protein-protein interaction confers specificity to a class of proteins whose DNA-recognition sequence is widespread in the genome. Sterols may repress transcription of the reductase gene by disrupting this protein-protein interaction.